Enrichment of Cu, Zn and Cd by Solid-Phase Extraction using Silica Gel Chemically Modified with Hydroxamic Acid Prior to Their Determination by Flame Atomic Absorption Spectrometry - Mohamad, Sharifah; Radzi Abas, M. (Malaysian Journal of Science, 2005)
An analytical method using silica gel chemically modified with hydroxamic acid (SG-CMHA) for the preconcentration of Cu, Zn and Cd, in a column system, and their sequential determination by flame atomic absorption spectrometry (FAAS), was developed. Different factors affecting the preconcentration including pH of sample solution, elution, flow rate of sample loading and elution, sample volume and matrix effects were examined. The optimum pH ranges for quantification sorption are 4.5-7.0, 5.5-7.0 and 5.5-7.5 for Cu, Cd and Zn, respectively. All the metal ions can be desorbed with 0.5 mol dmÃ¢ÂÂ»Ã‚Â³ HNOÃ¢â€šÆ’. Sample solutions are passed through column at flow rate of 2.0 ml minÃ¢ÂÂ»Ã‚Â¹ and flow rate of 1.0 ml minÃ¢ÂÂ»Ã‚Â¹ was chosen for stripping off the metal ions from the sorbent material. The highest preconcentration factor was found to be 150 for Cu, 200 for Zn and 100 for Cd. The relative standard deviations of the determination were below 5%. The limit of detection (3ÃÆ’, n= 10) for analytes were 1.20, 0.80 and 0.60 Ã‚Âµg lÃ¢ÂÂ»Ã‚Â¹ for Cu, Zn and Cd, respectively. The proposed method was evaluated with certified reference materials SLRS-4 and was applied to the analysis of Malaysian natural waters.